Thrombin Receptor Occupancy Modulates Aggregation Efficiency and Platelet Surface Expression of vWF and Thrombospondin at Low Thrombin Concentrations - Kasirer-Friede, Ana; Legrand, Chantal; Frojmovic, Mony M. (Thrombosis and Haemostasis, 1999)
Previous studies evaluating requirements for occupancy of thrombin receptors in normal platelet secretion and aggregation, using the thrombin antagonists hirudin and PPACK (D-Phe-Pro-Arg-chloromethylke-tone), have suggested that at low thrombin activating concentrations (0.025–0.13 U/ml), occupancy was required only in the first 45–60 s following activation. In our study, we differentiate between thrombin receptor occupancy requirements for surface expression of secreted adhesive proteins, for activation of GPIIb-IIIa receptors, and for aggregation of washed platelets (WP) in laminar shear flow. Platelets activated with 0.05 U/ml thrombin for 10 min to allow maximal secretion (hereafter referred to as “pre-activated platelets”), then sheared, showed a 50–70% decrease in platelet counts after 60 s of shear. Treatment of pre-activated platelets with hirudin or PPACK produced a 65% reduction of capture efficiencies, αG (reflecting experimental/theoretical initial rates of aggregation), as well as a 30–40% decrease in the surface expression of von Willebrand factor (vWF) and thrombospondin (TSP). However, α-granule membrane P-selectin expression and numbers of activated GPIIb-IIIa receptors were comparable for treated and non-treated platelets. No significant difference in any of the parameters tested was observed when platelets were similarly pre-activated with 0.2 U/ml thrombin, due to treatment with thrombin antagonists. Binding of soluble FITC-vWF (GRGDSP-sensitive) to pre-activated, thrombin antagonist treated platelets, was greatly reduced (≥80%). Soluble Fg was shown to bind to antagonist-treated pre-activated platelets, but could not significantly enhance platelet aggregation. Although occupancy of thrombin receptors by catalytically active thrombin is required transiently for secretion and activation of platelets, there is a further requirement for thrombin occupancy at low thrombin concentrations, for optimizing initial rates of platelet aggregation, surface expression of vWF and TSP, and activated GPIIb-IIIa ligand recognition.